Emissions of C6–C8 aromatic compounds in the United States: Constraints from tall tower and aircraft measurements. Issue 2 (24th January 2015) - Hu, Lu; Millet, Dylan B.; Baasandorj, Munkhbayar; Griffis, Timothy J.; Travis, Katherine R.; Tessum, Christopher W.; Marshall, Julian D.; Reinhart, Wesley F.; Mikoviny, Tomas; Müller, Markus; Wisthaler, Armin; Graus, Martin; et al.
Abstract We present two full years of continuous C6–C8 aromatic compound measurements by PTR‐MS at the KCMP tall tower (Minnesota, US) and employ GEOS‐Chem nested grid simulations in a Bayesian inversion to interpret the data in terms of new constraints on US aromatic emissions. Based on the tall tower data, we find that the RETRO inventory (year‐2000) overestimates US C6–C8 aromatic emissions by factors of 2.0–4.5 during 2010–2011, likely due in part to post‐2000 reductions. Likewise, our implementation of the US EPA's NEI08 overestimates the toluene flux by threefold, reflecting an inventory bias in non‐road emissions plus uncertainties associated with species lumping. Our annual top‐down emission estimates for benzene and C8 aromatics agree with the NEI08 bottom‐up values, as does the inferred contribution from non‐road sources. However, the NEI08 appears to underestimate on‐road emissions of these compounds by twofold during the warm season. The implied aromatic sources upwind of North America are more than double the prior estimates, suggesting a substantial underestimate of East Asian emissions, or large increases there since 2000. Long‐range transport exerts an important influence on ambient benzene over the US: on average 43% of its wintertime abundance in the US Upper Midwest is due to sources outside North America. Independent aircraft measurements show that the inventory biases found here for C6–C8 aromatics also apply to other parts of the US, with notable exceptions for toluene in California and Houston, Texas. Our best estimates of year‐2011 contiguous US emissions are 206 (benzene), 408 (toluene), and 822 (C8 aromatics) GgC.